Jordan Housing Sector Review - World Bank Group (World Bank, Washington, DC, 2019)
This report aims to support the Government of Jordan (GoJ) in improving housing sector performance. In 2016, the Hashemite Kingdom of Jordan requested the World Bank’s technical support to develop a housing sector review to update the Housing Strategy adopted in 1989. Given the enormous challenges currently facing the housing sector, the preparation of this housing sector review and its related recommendations is both timely and important to position the sector to respond effectively to a much-changed situation. The objective of the Jordan Housing Sector Review is to inform the development of a better functioning and more coordinated housing system in Jordan, which caters to the needs of the different segments of the population. This report tackles these and other challenges and questions by taking a comprehensive look at the housing market and conditions in Jordan. It looks at the country context, identifying the role of housing in the economy today and the sector’s contribution to Gross Domestic Product (GDP) and employment. It also takes a close look at previous housing strategies and housing programs, analyzing the current institutional framework and housing ecosystem. Also, analytical work has been undertaken to review the market response to the crisis in terms of housing production, as well as impacts on vacancies, tenure, the housing deficit and affordability of ownership and rental markets. The report looks into the current demand by size and location, and future demand by projecting household formation over the next two decades including consideration of possible refugee flows. A housing supply value chain along with a commercial finance for housing supply and demand analysis is part and parcel of this report. The report includes a set of recommendations crafted to each of the findings presented along the report, aiming to support the government to make inform decisions and to develop the aspired new housing strategy. Conscious of the current fiscal constraints of the GoJ, the recommendations have been prioritized to those that do not increase government expenditures or reduce government revenues in the short term. This report has been led by the Minister of Public Works and Housing (MPWH) in collaboration with the Housing and Urban Development Corporation (HUDC) and the World Bank. Talal Abu Ghazaleh (TAG-Consulting) consulting firm was hired by the GoJ to contribute with technical papers on the different topics covered and presented in this report.